Pengaruh Bullying Terhadap Perkembangan Anak - Ai Nurmafalah; Ageng Saepudin Kanda (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
Basically, each human individual is unique, each one is different from the others. So each human always has its own characteristics and characteristics that differentiate it from other humans. Due to this uniqueness, deviant things or actions often occur in everyday life between peer groups. The peer group should be the second environment after the family, which has a major influence on an individual's life. Peer groups provide an environment, namely a place where peers can socialize with applicable values, no longer values ​​set by adults, but by friends of their age and place in order to determine their identity, but if the values ​​developed in a peer group are values ​​or negative behavior will pose a danger to the development of the individual's soul.